A STUDY OF MISUNDERSTANDINGS AS A MEANS OF FINDING LOVE THEME IN WILLIAM SHAKESPEARE’S TWELFTH NIGHT - Ali Fauzi (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2019)
Misunderstanding can happen to everyone, either male or female, young or old. It happens to human beings in daily life, as a reflection of their genuine characteristics, that is fault and forgetfulness. The existence of them will not only set up misunderstandings but may bring about bad and good quality as well. As social beings, ones must make contact with others in their community. This kind of contact is the primary cause of the existence of misunderstanding. Literature, as the expression of the real life, of course, covers the whole human activities including misunderstanding, its cause and its effect. Shakespeare’s Twelfth Night, is a comic story meant to amuse the readers or audiences through misunderstandings and comical circumstances leading to the appearance of some mistakes. Misunderstandings are mostly caused by the disguise of Viola as a boy. Because of the mystery, Antonio accuses her of being ungrateful and claims her to return the purse he gave before. Sir Andrew and Sir Toby attack her and Sebastian by mistake. Malvolio thinks her a gentleman when she is delivering messages and love letters to Olivia. The peak of all is that Olivia falls in love with Viola. She is sure that Viola is a real good-looking boy. She, Olivia, marries Sebastian by mistake. Meanwhile, Orsino who realizes that Olivia has got married with Sebastian, marries Viola in the end. The four main characters become two pairs of newly married couples and live happily. Sebastian lives happily with Olivia and Orsino lives peacefully with Viola. Misunderstandings have close relationship with the theme, the main idea. It can be a means of finding theme of the story by analyzing every happening of the play. So, there is a relationship of cause and effect between misunderstanding and theme, as one unity supporting one another. Misunderstandings causing the conflicts among characters become the way to find love theme of the story through analyzing all subject matters. It means misunderstandings can bring about love and marriage between them, primarily the main four characters and they lead to love theme of the story.